Migrant older adults’ perception of social support on subjective well-being: a mediating role of psychological resilience - Liu, Yuxi; Liu, Qian; Gan, Qihui; Jia, Li; Zhu, Xianglei; Liu, Ruiming; Huang, Jie; Wan, Chonghua; Chen, Qikang (Frontiers in Public Health, 2025)
IntroductionWith the acceleration of urbanisation in China, there are a growing number of migrant older adults, and the mental health problems of this group require prompt attention.MethodsThis research conducted a questionnaire survey of 470 migrant older adults in various communities of Dongguan, and employed an independent sample t-test, Pearson correlation analysis, and stepwise multiple regression to analyse the data to explore the relationship between perceived social support, resilience and subjective well-being (SWB).ResultsThe findings indicated that migrant older adults’ perceived social support is positively correlated with resilience (r = 0.827, p < 0.05) and SWB (r = 0.645, p < 0.05), and resilience and SWB are also positively correlated (r = 0.698, p < 0.05). The SWB of migrant older adults can be predicted from their perceived social support (β = 0.182, p < 0.05) and resilience (β = 0.281, p < 0.05). Moreover, resilience partially plays a mediating role between the perception of social support and SWB, and the mediating effect accounts for 60.8 percent of the total effect.DiscussionTo improve the SWB of the migrant older adults, it is important to address the psychological potential of the migrant older adults from the perspective of positive psychology, and help them improve their positive psychological quality and resilience.